2016
DOI: 10.1053/j.gastro.2016.06.051
|View full text |Cite
|
Sign up to set email alerts
|

A Pleiotropic Missense Variant in SLC39A8 Is Associated With Crohn’s Disease and Human Gut Microbiome Composition

Abstract: BACKGROUND & AIMS Genome-wide association studies (GWAS) have identified 200 inflammatory bowel disease (IBD) loci, but the genetic architecture of Crohn’s disease (CD) and ulcerative colitis (UC) remains incompletely defined. Here we aimed to identify novel associations between IBD and functional genetic variants using the Illumina ExomeChip. METHODS Genotyping was performed in 10,523 IBD cases and 5,726 non-IBD controls. 91,713 functional single nucleotide polymorphism (SNP) loci in coding regions were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 54 publications
6
108
0
2
Order By: Relevance
“…SLC39A8 is required during cardiac development and regulates zinc transport in endothelium (49). Recent studies also highlight a role for the SLC39A8 common variant in regulation of the gut microbiome and metal homeostasis in Crohn's disease (4,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…SLC39A8 is required during cardiac development and regulates zinc transport in endothelium (49). Recent studies also highlight a role for the SLC39A8 common variant in regulation of the gut microbiome and metal homeostasis in Crohn's disease (4,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Top pleiotropic SNPs included (1) rs13107325, a non-synonymous SNP in the gene SLC39A8, which was fine-mapped for balding, BMI, diastolic blood pressure, forced vital capacity, height, red blood cell count, total cholesterol, and waist hip ratio (adjusted for BMI); (2) rs1229984, a nonsynonymous SNP in the gene ADH1B, which was fine-mapped for BMI, LDL, mean corpuscular hemoglobin, mean platelet volume, systolic blood pressure, total cholesterol, and Vitamin D; and (3) rs76895963, a conserved intronic SNP in a promoter of the gene CCND2, which was fine-mapped for bone mineral density, height, red blood cell count, systolic blood pressure and triglycerides. The gene SLC39A8 is a zinc transporter and is associated with congenital disorder of glycosylation 36,37 ; the gene ADH1B is an alcohol dehydrogenase gene and is associated with alcohol dependence 38 ; and the gene CCND2 participates in cell cycle regulation and is associated with delayed psychomotor development 39 . We note that previous studies have reported that genetically uncorrelated traits often share association signals at the same loci 40 , but did not fine-map those signals to individual SNPs as performed here.…”
Section: Functionally Informed Fine-mapping Of 47 Complex Traits In Tmentioning
confidence: 99%
“…The first such studies in humans focused on specific genes and pathways, and have identified several significant microbiome-associated variants [41][42][43][44][45]. However, a potential shortcoming of the above studies is that they require previous knowledge of associated genes, and thus cannot discover new associations.…”
Section: Limited Power Of Microbiome Genome Wide Association Studiesmentioning
confidence: 99%